Hand-to-Face Remapping But No Differences in Temporal Discrimination Observed on the Intact Hand Following Unilateral Upper Limb Amputation - Collins, Kassondra L.; McKean, Danielle L.; Huff, Katherine; Tommerdahl, Mark; Favorov, Oleg Vyacheslavovich; Waters, Robert S.; Tsao, Jack W. (Frontiers in Neurology, 2017)
Unilateral major limb amputation causes changes in sensory perception. Changes may occur within not only the residual limb but also the intact limb as well as the brain. We tested the hypothesis that limb amputation may result in the detection of hand sensation during stimulation of a non-limb-related body region. We further investigated the responses of unilateral upper limb amputees and individuals with all limbs intact to temporally based sensory tactile testing of the fingertips to test the hypothesis that changes in sensory perception also have an effect on the intact limb. Upper extremity amputees were assessed for the presence of referred sensations (RSs)—experiencing feelings in the missing limb when a different body region is stimulated, to determine changes within the brain that occur due to an amputation. Eight of 19 amputees (42.1%) experienced RS in the phantom limb with manual tactile mapping on various regions of the face. There was no correlation between whether someone had phantom sensations or phantom limb pain and where RS was found. Six of the amputees had either phantom sensation or pain in addition to RS induced by facial stimulation. Results from the tactile testing showed that there were no significant differences in the accuracy of participants in the temporal order judgment tasks (p = 0.702), whereby participants selected the digit that was tapped first by a tracking paradigm that resulted in correct answers leading to shorter interstimulus intervals (ISIs) and incorrect answers increasing the ISI. There were also no significant differences in timing perception, i.e., the threshold accuracy of the duration discrimination task (p = 0.727), in which participants tracked which of the two digits received a longer stimulus. We conclude that many, but not all, unilateral upper limb amputees experience phantom hand sensation and/or pain with stimulation of the face, suggesting that there could be postamputation changes in neuronal circuitry in somatosensory cortex. However, major unilateral limb amputation does not lead to changes in temporal order judgment or timing perception tasks administered via the tactile modality of the intact hand in upper limb amputees.